Get rich with dividends : a proven system for earning double-digit returns - Lichtenfeld, Marc (Wiley, 2015)
Notes; Chapter 4 Why Companies Raise Dividends; Buybacks versus Dividends; Management Speaks; Attracting the Right Shareholders; Signals to the Market; Summary; Notes; Chapter 5 Get Rich with Boring Dividend Stocks (Snooze Your Way to Millions); How Much Do You Want to Make?; Summary; Note; Chapter 6 Get Higher Yields (and Maybe Some Tax Benefits); Buying 1 in Assets for 0.90; MLPs; REITs; BDCs; You Don't Have to Play Mahjong with Mrs. Zuckerberg; Preferred Stocks; Summary; Chapter 7 What You Need to Know to Set Up a Portfolio; The Oxford Income Letter Portfolio-An Example.